Women’s Cigarette and Marijuana Use in Pregnancy: Identifying the Role of Past Versus Recent Violence Exposure - Miller-Graff, Laura E. (Journal of interpersonal violence, 2021)
Both cigarette smoking and marijuana use during pregnancy pose serious risks to healthy fetal development, yet little is known about the comparative contribution of recent versus past traumatic experiences to women’s smoking behavior. The current study aimed to examine the relative contributions of childhood adversity and past year intimate partner violence (IPV) to women’s cigarette and marijuana use during pregnancy in a high-risk, low-income sample. Participants (n = 101) were interviewed to evaluate past year IPV, childhood adversity, and cigarette and marijuana use. Results indicated that approximately one in four pregnant women in the sample reported that they were currently smoking cigarettes. Only a minority of those who reported prepregnancy smoking (22.5%) were able to quit smoking once pregnant. Regarding marijuana use, 6.9% of women reported use during pregnancy, with 68.1% of women using prior to pregnancy ceasing use once pregnant. Results of multinomial regressions controlling for income and education indicated that past year physical abuse by a partner was associated with light cigarette use during pregnancy whereas high rates of childhood adversity were associated with moderate cigarette use during pregnancy. Sexual IPV was associated with marijuana use during pregnancy. Comprehensive assessment of women’s history of exposure to violence, including both past and recent exposure, provides insight into which women may have the most difficulty with unassisted cessation in the prenatal period. Providing better intervention and support around cigarette and marijuana cessation for women exposed to violence is a critical need, especially among groups that are at sociodemographic risk for substance use in pregnancy.